2021
DOI: 10.1016/j.jve.2021.100033
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HIV burden in the inflamed and non-inflamed colon from a person living with HIV and ulcerative colitis

Abstract: The greatest obstacle to an HIV cure is the persistence of latently infected cellular reservoirs in people living with HIV (PLWH) taking antiretroviral therapy (ART). However, no consensus exists on the direct link between local tissue inflammation and the HIV burden. Herein, we have compared the levels of local inflammation, epithelial integrity and HIV DNA between inflamed and non-inflamed colon tissue in a PLWH who underwent a colectomy due to ulcerative colitis. We have observed a 27-fold higher frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…However, the effect of IFN-a on T cells during persistent infection remains controversial [82]. Studies showed that blocking all signalling through IFNAR was beneficial to T cells; however, it also resulted in higher viral loads and drove the immune activation associated with greater reservoir size [83,84]. Since IFN-a2 is the predominant subtype during HIV-1 infection [30] it may be the primary contributor to deleterious IFNAR signalling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of IFN-a on T cells during persistent infection remains controversial [82]. Studies showed that blocking all signalling through IFNAR was beneficial to T cells; however, it also resulted in higher viral loads and drove the immune activation associated with greater reservoir size [83,84]. Since IFN-a2 is the predominant subtype during HIV-1 infection [30] it may be the primary contributor to deleterious IFNAR signalling.…”
Section: Discussionmentioning
confidence: 99%
“…However, their effect on CD4 + levels should be assessed (Hunt et al 2021 ). It was also concluded that HIV persistence in UC could be challenged through a strong gut barrier integrity and reduction of inflammation (Peng et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…These bacterial and fungal translocations are associated with systemic immune activation and tissue inflammation (109). Cells in inflamed gut tissue are described as having a 27-fold higher frequency of HIV DNA than cells in non-inflamed gut tissue (110). This immune activation and inflammation is thought to lead to an increase in the frequency of other conditions such as metabolic and cardiovascular diseases (111).…”
Section: Intestinal Barrier Functionmentioning
confidence: 99%